Pengaruh Penambahan Limbah Plastik Polyethylene Terephthalate (PET) terhadap Karakteristik Campuran Aspal Porus Menggunakan Aspal PG 70 - Sugiarto, Moch Rizqi; Rizkiardi, Aditya (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Porous asphalt is an open-graded asphalt mixture with high air voids that allows water to flow through the pavement layer. This study aims to evaluate the effect of adding Polyethylene Terephthalate (PET) plastic waste on the characteristics of porous asphalt mixtures. The study was conducted experimentally using Performance Grade (PG) 70 asphalt via the dry mixing method with PET content variations of 0%, 2.5%, 5%, and 7.5% by weight of the asphalt. Testing was based on AAPA (2004) specifications with an Optimum Asphalt Content (OAC) of 6%. The analyzed parameters included Marshall Stability, Flow, Marshall Quotient, Cantabro Loss, Asphalt Flow Down, and Permeability. The results showed the highest stability of 1245.81 kg at a PET content of 7.5% and the lowest Cantabro Loss of 7.32% at a PET content of 2.5%. Permeability values ranged from 0.13–0.15 cm/s. Overall, a PET content of 2.5% provided the most optimal mixture performance.